Fortification System of Hellenistic States of Baktria. The Great Baktrian Wall of Antiochos I and Euthydemos I - Rtveladze, Edvard V. (Anabasis. Studia Classica et Orientalia, 2020)
The Great Baktrian Wall was created and functioned for several centuries, primarily to delineate the northernmost border of the Seleukid realm, and later that of the Greco-Baktrian kingdom. Its most important function was to protect this border from an invasion of nomads from the north. It was part of a centralized system of defense that protected the state borders of Hellenistic Baktria, the northern part of which consisted of two lines. The first, which actually constituted the Great Baktrian Wall per se, passed through the western portion of the Hissar Mountains. The second line passed along the river Oxos, protecting its most important crossings near Kampyrtepa, Kelif, Termez, and quite probably Kerki.